Agile strategy management techniques for continuous alignment and improvement - Lyngso, Soren (ESI international project management series ;, 2014)
Your strategic initiatives are constantly under fire due to the evolving nature of markets, technology, laws, and government. To ensure your strategy succeeds, it must remain flexible while confronting these shifting challenges. Agile Strategy Management: Techniques for Continuous Alignment and Improvement explains how to achieve this flexibility by building agility into the initiation, development, implementation, and governance of your strategic initiatives.